How much is too much? Estimating tourism carrying capacity in urban context using sentiment analysis. (August 2022) - Tokarchuk, Oksana; Barr, Jacob Charles; Cozzio, Claudia
Abstract: Although the crisis caused by COVID-19 has drastically reduced tourism in many renowned destinations, the hopes of a return to normality are also associated with subdued fears of large crowds invading touristic spots once tourism resumes. The primary concern expressed by destination managers is that overcrowding during the recovery may deteriorate tourists' experience. The present paper aims to develop an innovative measure of destinations' carrying capacity based on sentiment analysis through Tripadvisor online reviews. The analysis pertains to the city of Berlin and covers the period from 2013 to 2019. This study develops an emotional index regressed on the tourism intensity registered in the destination during the period examined. Two measures of carrying capacity, based on positive and negative emotion indices, are derived. Carrying capacity based on a negative index is lower than the one based on a positive index. Findings prove that destination managers can use the emotional index for measuring the carrying capacity of the destination.